Estimation of the hidden demand for health services: a support for Peruvian social insurance - Caparó, Rafael (2017)
The importance of the health sector is closely related to social welfare, since thinking about the health sector means thinking about a series of alternatives for improvement. Many of the hospitals that are built for the health sector are saturated with demand as soon as they are finished, this is a problem that may be associated with an erroneous perception of the demand for health services and that can be reflected in social unrest if it is not well calculated, in this sense, building a model that can nest the expectations of hospital saturation (logistics) with the hidden demand for health services is a great challenge for this research. As has been done in other countries, we will perform an econometric model to determine the additional percentage that should be considered when building a health center due to hidden demand, without generalities this model can be applied to other types of social services. This is the third report and complements the research with tables and results.